2015
DOI: 10.4172/2329-6879.1000225
|View full text |Cite
|
Sign up to set email alerts
|

Making Economic Social Decisions for Improving Occupational Health – A Predictive Cost-Benefit Analysis

Abstract: The few studies attempting to estimate costs of work-related disorders suffer from poor applied methodologies. Further, as the costs are often limited to the company, decisions about investment in improving the work environment are made at the company level. However, economic decisions on changing work environments and improving occupational health need to be made at the societal level. In an economic social decision, all direct and indirect costs imposed on society by work-related disorders are considered, re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(26 citation statements)
references
References 26 publications
0
25
0
1
Order By: Relevance
“…Satisfied and productive employees are necessary to create a successful company, while dissatisfied and unproductive workers jeopardize the company’s image, sustainability, competitiveness, and survival [ 1 ]. The well-being and productivity of the workforce is conditional on a well-functioning work environment with minimum risk factors for illness [ 1 – 6 ].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Satisfied and productive employees are necessary to create a successful company, while dissatisfied and unproductive workers jeopardize the company’s image, sustainability, competitiveness, and survival [ 1 ]. The well-being and productivity of the workforce is conditional on a well-functioning work environment with minimum risk factors for illness [ 1 – 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Satisfied and productive employees are necessary to create a successful company, while dissatisfied and unproductive workers jeopardize the company’s image, sustainability, competitiveness, and survival [ 1 ]. The well-being and productivity of the workforce is conditional on a well-functioning work environment with minimum risk factors for illness [ 1 – 6 ]. Many disorders in a company are related not only to the physical environment at the workplace [ 2 – 7 ], but also to the work conditions along a series of psychosocial and ergonomic factors that characterize the work culture in the company [ 1 – 6 , 8 – 13 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…work-related disorders [36]. In October 2015, a work environmental study involving 100 workers was suggested to SMT.…”
Section: The Suggested Work Environmental Studymentioning
confidence: 99%